Productive Signs: Improving the Prospects of Peirce’s Rhetoric - Bergman, Mats (Signs - International Journal of Semiotics, 2010)
Studies of C. S. Peirce’s theory of signs have typically focused on the sub-disciplines he branded grammar and critic, with comparably little attention paid to the third semiotic branch, that is, to the line of inquiry he identified as rhetoric or methodeutic. However, Peirce’s elevation of rhetoric to the status of the highest division of logic should not be ignored; the future prospects of his sign-theoretical project are arguably closely tied to the conceptualisation and development of the third branch. This article traces the development of Peirce’s rhetoric and explores the tension between the rhetorical and methodeutic perspectives in his mature theory of signs, with the aim of preparing the way for a re-evaluation of the hierarchy of sign-theoretical disciplines. The article concludes with a sketch for a rhetorical approach to Peircean sign theory.